Research on the Weighted-factors-based Synchronization Method for OFDM - Tian, Ye; Tan, Zhenhui; Zhu, Gang (2006 8th international Conference on Signal Processing, 2006)
In this paper, the weighed-factors-based synchronization algorithm for OFDM proposed by reference (Chunlin Yan et al., 2004) is studied. By theory analysis and computer simulation, a conclusion is drawn: in AWGN channel, the weighed-factors-based algorithm can choose the PN sequence freely, as long as the PN sequence is known to the receiver. But in multipath channel, the weighed-factors-based algorithm cannot choose the PN sequence as freely as in the AWGN channel. Instead, the selection of the PN sequence must meet some conditions, otherwise the accuracy of frequency estimation will be reduced